Investigation on the Role of Drying Air Humidity and Process Parameters in Shaping the Conditions of Spray Drying Using Model Feed Materials - Alicja Barańska-Dołomisiewicz; Aleksandra Jedlińska; Katarzyna Samborska (Applied Sciences)
A three-stage research using distilled water and maltodextrin as model feed solutions was conducted to study the influence of inlet air humidity on spray drying performance. In the first and second stage, spray drying of distilled water and 30% (solids, w/w) MD solutions were tested at variable feed rate (0.16–0.83 mL/s), inlet air humidity (0.1–0.3, 1.1–1.3, 9–10 g/m3) and inlet air temperature (80–120 °C). In the third stage, the optimization of MD solutions spray drying process variables (80–120 °C inlet air temperature, 0.1–0.3, 1.1–1.3, 9–10 g/m3 inlet air humidity, 10–30% feed solution concentration) were verified for maximum powder recovery and powders of low moisture content and activity. It was noted that inlet air humidity influenced the spray drying performance. Reduced humidity improved the process conditions, but the most satisfying powder properties were noted at 120 °C, thus decreasing inlet air temperature was not necessary to ameliorate the process performance. Optimization in the third stage of the study enabled us to estimate the most satisfying properties of maltodextrin powders. The highest powder recovery and the lowest moisture content and water activity were optimal for spray drying at inlet air temperature of 120 °C, inlet air humidity of 0.1 g/m3, and feed solution concentration of 29.571%.